Mapping Students’ Science Literacy Skills Using Local Wisdom-Based Physics Instruments - Alhusni, Hanan Zaki; Prahani, Binar Kurnia; Sunarti, Titin; Madlazim, Madlazim; Kurtuluş, Muhammed Akif (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study addresses Indonesian students’ low scientific literacy (PISA 2022) by developing and validating a Tari Boranan Lamongan–contextualized physics assessment instrument on rigid body equilibrium. Existing PISA-aligned tests are rarely embedded in local culture. At the same time, local wisdom materials often do not measure all eight PISA scientific literacy indicators, creating a gap for culturally resonant yet comprehensive diagnostic tools. This study aimed to (1) develop and validate an eight-indicator, PISA-aligned scientific literacy instrument, (2) map Grade XI students’ literacy profiles across the eight indicators, and (3) explore how the Boranan context shapes students’ engagement and reasoning. Using a mixed-method embedded design, 73 Grade XI students in Lamongan Regency completed eight essay-based literacy tasks, and ten students participated in semi-structured interviews. Expert validation indicated high content relevance, cultural authenticity, and indicator alignment, and reliability analysis yielded Cronbach’s alpha = 0.82. Results showed most students were in the very low and low categories, with relative strengths in interpreting data (45%) and explaining phenomena (38%), but pronounced weaknesses in designing investigations (28%), evaluating credibility of information (25%), and making evidence-based decisions (30%). Interviews confirmed that cultural context enhanced engagement and visualization but did not automatically support mathematical formalization. These findings suggest that the instrument can be used diagnostically to help teachers design targeted scaffolding for higher-order literacy skills, particularly in investigation design, credibility evaluation, and evidence-based decision-making, within culturally responsive physics learning.